Stuck in neutral: A case study of the challenges facing the Kenyan automotive sector - Makundi, Brian (School of Economics, 2018)
Successful industrialisation strategies have helped many developing countries transform the structure of their economies, enhance productivity and boost economic growth. Prioritising which industrial sectors to develop, and how, is paramount given scarce financial resources, skills shortages and limited technological capabilities. Although still a developing country, Kenya has the most advanced economy among her regional peers. Kenya's small automotive sector was established four decades ago with the support of import substitution industrialisation (ISI) policies. However, following liberalisation of the economy in the last decade of the 20th century, domestic industries were suddenly exposed to competition from imported products. On one hand this blunted prospects for faster development of manufacturing capabilities, but on the other, imports provided consumers with affordable alternatives. As a result, the domestic automobile assembly sector faces ongoing competition from used passenger vehicle imports. Fundamentally, the sector lacks access to a sizeable market, which inhibits attraction of large-scale investments necessary for upgrading. Market attributes aside, this study found several other challenges confronting the sector. These are; the absence of a national automotive strategy, incoherent policy decisions and ineffective regional integration which has hampered growth beyond national borders. Additionally, weak support for higher levels of domestic value addition in the auto components and motorcycle sectors has been exacerbated by fierce competition from Asian producers. Recent interventions to restart passenger vehicle assembly have only spurred superficial development notwithstanding some government support. The challenges facing late industrialisers are multi-dimensional with near term solutions difficult to discern - the small Kenyan automotive sector is emblematic of this.